FAKTOR-FAKTOR YANG MEMPENGARUHI MOTIVASI KERJA DAN KEPUASAN KERJA PADA PEKERJA BERKETERAMPILAN RENDAH ATAU TERBATAS - Diah Pradiatiningtyas (Universitas Trisakti, 2007)
This paper examined factors that influence work motivation and satisfaction. The research focus on employee with low or limited skills and education, they don't have career on the job and paid with minimum salary. This employee do not have any opportunities or gain job promotion. There is a reality faced by them because of their limited skills and education, while they have to serve the customer better. The interesting point to be investigated was the factors influencing their motivation in work besides salary they expected. The company face dilemma whenever they needs this type of employee but they have to maintain the employee with minimum salary to reduce intention to quit. Linear reggression conducted to examine the influences of leadership, condition of work, and employee internal factors to work motivation and satisfaction. The construct was adapted and developed from the model of Nordic Employee Index. The result shows that internal factors were the most influencing variable to work motivation and satisfaction.Keywords : Condition of work, Leadership, Motivation, Satisfaction